The effects of FTO gene rs9939609 polymorphism on the association between colorectal cancer and dietary intake - Gholamalizadeh, Maryam; Jonoush, Mona; Mobarakeh, Khadijeh Abbasi; Amjadi, Arezoo; Alami, Farkhondeh; Valisoltani, Neda; Askarpour, Seyed Ali; Azizi-Tabesh, Ghasem; Mohammadian, Mohammad Keshavarz; Akbari, Mohammad Esmail; Rajabibazl, Masoumeh; Alemrajabi, Mahdi; et al. (Frontiers in Nutrition, 2023)
Background: FTO gene is associated with obesity, dietary intake, and the risk of colorectal cancer (CRC). In this study, patients with colorectal cancer were assessed for the interactions between FTO gene polymorphisms and dietary intake. Methods: This case-control study was carried out on 450 participants aged 35-70 years including 150 patients with colorectal cancer and 300 healthy controls. Blood samples were collected in order to extract DNA and genotyping of FTO gene for rs9939609 polymorphism. A validated 168-item food frequency questionnaire (FFQ) and the Nutritionist-IV software were used to assess dietary intake. Results: In the participants with the TT genotype of FTO rs9939609 polymorphism, CRC risk was significantly associated with higher intake of dietary fat (OR:1.87 CI95%:1.76-1.99, P=0.04), vitamin B3 (OR:1.20 CI95%:1.08-1.65, P=0.04), and vitamin C (OR:1.06 CI95%:1.03-1.15, P=0.04) and lower intake of β-carotene (OR: 0.98, CI95%:0.97-0.99, P=0.03), vitamin E (OR:0.77 CI95%:0.62-0.95, P=0.02), vitamin B1 (OR:0.15 CI95%:0.04-0.50, P<0.01), and biotin (OR:0.72 CI95%:0.0.57-0.92, P=0.01). No significant association was found between CRC and dietary intake in carriers of AA/AT genotypes after adjustments for the confounders. Conclusion: CRC risk may be decreased by β-carotene, vitamins E, B1, and biotin only in those without the risk allele of the FTO gene. The association of CRC and diet may be influenced by FTO genotype. Further studies are warranted.